Community resilience for urban flood-prone areas: a methods paper on criteria selection using the Fuzzy Delphi method. (6th August 2021) - Ali, Sameer; George, Abraham
Abstract : Purpose: Community resilience decides a lot on a city's ability to withstand an external shock. It has evolved naturally from a bounce-back approach to a more robust and meaningful bounce-forward process. The study explores gaps found in community resilience and finds that criteria specific to different disasters are absent. Design/methodology/approach: The study uses a multi-criteria decision analysis technique, fuzzy Delphi, to select criteria. Derivation of the initial list of criteria was from a pilot study, a focus group discussion and other literature studies which was followed by the fuzzy Delphi survey. Findings: After two rounds of fuzzy Delphi analysis, the consensus among 65 experts resulted in selecting 125 sub-sub-criteria within seven criteria. Findings show that many criteria previously not discussed in other pieces of literature project high fuzzy scores such as "availability of drinking water post-disaster" and "cracking down fake news spreaders by the police". In addition, positive cooperation between political and religious institutions have proven to expedite disaster recovery. Research limitations/implications: The future scope also includes weighing the selected criteria using analytical hierarchy process (AHP). Practical implications: Policymakers in the disaster management domain can use the study findings in implementing effective disaster mitigation strategies. Originality/value: The selection of criteria is based on the community resilience shown by the Kerala community during the floods of 2018 and 2019 (in Kerala). Measures demonstrated by the community need to be studied, which will help foster disaster mitigation better in future scenarios.